The beauty of Crystalline Glaze by Oryza Sativa Straw Ash / Amirulazani Ibrahim... [et al.] - Ibrahim, Amirulazani; Awang, Nor Nazida; Ayob, Salwa; Vermol, Verly Veto (UiTM Perak Press, 2021)
Glazes are put onto ceramic to colour, or protect the surface, allowing it to be used for many different functions (Fairbairn, 1999). There are many types of glazes, designed for a variety of applications and firing at different temperature ranges such as special effects glazes like matt glazes, satin glaze, crystalline glaze, crackle glaze and others. There is also a wide variance in the appearance of finished glazes. That glazes must be designed to fit a specification (Taylor & Bull, 1986). There are two major types of crystalline glazes. Micro crystalline, which have crystals so small that need a microscope to see, and macro crystalline, which have crystals large enough to be seen with the naked eye. The type of glaze which is central to this study is the macro crystalline glaze or more commonly, the crystalline glaze. However, since the beginning of the 19th century ago until now, crystalline glaze is gaining attention as a coating on the ceramic body to be able to provide aesthetic value to the body. In addition, many studies have been carried out in respect of these glazes (Creber, 1997; Karasu et al., 2001; Karasu et al., 2000; Karasu & Turan, 2002; Knowles & Freeman, 2004). Apart from identifying the effects of adding rice straw ash (RSA) in crystalline glaze, this research was conducted to identify a method that may reduce the firing temperature of crystalline glaze but still be able to produce crystal formation with various patterns. Therefore, the use of certain raw materials in glaze formulations has been identified as one of the appropriate methods. The use of alkali metals such as lithium, sodium, and potassium as well as alkaline earth metals calcium, barium, magnesium, and strontium are found to be suitable because they act as flux. Generally, the function of flux is to lower the melting point of frit and glaze by adding fluidity to Tgloss as well as increasing production of glaze. Crystalline glaze is chemically known as zinc-silicate crystals. According to Draney, (1969), he said in his study about macro crystalline glaze, crystals form an ionic bond between zinc and silica. Hence, silica is course of the principal acidic oxide and the basis of all glazes since it is a glass former. In crystalline glazes silica functions as it does in conventional glazes and is proportioned to control the melting temperature of the glaze. Silica is also bond with zinc oxide to form the crystalline seed structure. From that, this study is to identify the possibility of replacing conventional silica in crystalline glaze formulation with rice straw ash.